2013
DOI: 10.9790/3013-034301-13
|View full text |Cite
|
Sign up to set email alerts
|

Histological Changes in Human Gallbladder in Pathological Condition Including Cholecystitis and Cholelithiasis an Analytical Study

Abstract: : Present study compares histological changes in the wall

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Pani et al found that a major amount of mucin in cholelithiasis and cholecystitis was sulfomucin and sialomucin, respectively. Similar to intestinal epithelium, the gallbladder also showed increased mucin secretion for stone formation and acceleration which leads to concomitant exhaustion of mucin content within the lining epithelium [ 14 , 15 ]. Finally, in this study, we found that inflammation causes mucin alteration, which is exactly opposite to normal gallbladder mucin.…”
Section: Discussionmentioning
confidence: 99%
“…Pani et al found that a major amount of mucin in cholelithiasis and cholecystitis was sulfomucin and sialomucin, respectively. Similar to intestinal epithelium, the gallbladder also showed increased mucin secretion for stone formation and acceleration which leads to concomitant exhaustion of mucin content within the lining epithelium [ 14 , 15 ]. Finally, in this study, we found that inflammation causes mucin alteration, which is exactly opposite to normal gallbladder mucin.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the enhanced intake of wealthy calories and fatty diet and increasing alcoholic consumption, the prevalence of cholecystitis and colelithiasis has risen globally over the previous couple of centuries. 2,3 The rate of gallstone disease differs depending on era, gender, ethnic groups and regions. In Americans and Indians, the incidence of gall liver in women is strong at 60% -70%; Chile (is a nation of South America) at 37%; the UK and the US at 6% to 12% and 11%, respectively, at 6 The incidence frequency of China and Japan is very small, 5%.…”
Section: Introductionmentioning
confidence: 99%
“…2 The incidence of cholecystitis and choleilithiasis has increased over the past couple of decades throughout the world and is attributed to the increased intake of fatty, high calorie diet and increased consumption of alcohol. 3,4 The prevalence of gall stone disease varies with age, sex, ethnic groups and geographical areas. The female prevalence of gall bladder disease in the American Indians and Pima Indians is as high as 60%-70%, Chile 37% while in UK and in the USA it is 6% to12% and 11% respectively.…”
Section: Introductionmentioning
confidence: 99%